Repeat urine cultures in children with urinary tract infection - Prasetyo, Risky Vitria; Soemyarso, Ninik Asmaningsih; Noer, Mohammad Sjaifullah (Paediatrica Indonesiana, 2012)
Background Urinary tract infections (UTIs) are the second leading cause of infection in children, following respiratory tract infections. Repeat urine cultures after antibiotic treatment are routinely obtained in clinical practice to verify proof of bacteriologic cure. The American Academy of Pediatrics does not recommended repeat cultures, due to increased cost and discomfort to patients. Objective To determine the frequency of positive repeat urine cultures after 3 days of antibiotics in children ’With UTIs. Methods We conducted a retrospective study on children with UTIs who visited the Division of Pediatric Nephrology, Department of Child Health at Dr. Soetomo Hospital, Surabaya from January 2006 to December 2011. Results of repeat urine cultures were obtained after 3 days of antibiotic treatment. Descriptive statistics were used to analyze the data. Results Of the 779 pediatric UTI cases, repeat urine cultures were performed in 264 (33.9%) cases. Of the 264 patients who comprised our study, there were similar numbers of girls and boys (50.4% vs. 49.6%, respectively). The mean age of patients was 43.9 (SD 1.59) months and 35.5% of subjects were aged under 1 year. In the initial urine cultures of our subjects, Escherichia coli was the most common organism found, v,ith 92 cases (34.8%), compared to 58 cases (21.9%) of Klebsiella pneumoniae and 29 cases (10.9%) of Pseudom.onas aeruginosa. Repeat urine cultures showed no bacterial growth in 168 cases (63.6%). Conclusion Mostly negative repeat urine cultures v,ill probably obviate the need of this test in daily routine practice. [Paediatr Indanes.2012,52:170Â·4].